FORMING PROFESSIONAL FOREIGN LANGUAGE COMPETENCY IN THE PROCESS OF FUTURE PETROLEUM ENGINEERS’ TRAINING - Tymkiv, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the issues of forming professional foreign language competency of future petroleum engineers. Interdisciplinary tasks of petroleum industry boost intensive international collaboration and intercultural cooperation. This necessitates development of professional foreign language competency required for both engineers and middle-ranking staff since it is a crucial factor in interdisciplinary and international team work training for the next generation of petroleum workers. It has been suggestededucational process design based on integrative approach and relevant principles.